Moebius Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1989)
Brain stem calcification on CT scan, suggesting prenatal brain stem ischemia, is reported in an infant with Moebius syndrome examined in the Department of Pediatrics and Neonatal Medicine, State University of Gent, Gent, Belgium.